Connections between land usage, property structure and agricultural enterprises in Hungary - Nagyné Demeter, Dóra (Acta Agraria Debreceniensis, 2006)
The last decade of Hungarian agriculture was marked and changes which affected all parts of agricultural production. This process resulted in a new ownership and organisation structure. The paper presents the effects of the changes in ownership on land use and the various enterprise forms and intends to outline the main tendencies. In general, it can be stated that the role of agriculture in GDP production and employment is decreasing in Hungary, but according to concurrent opinions of experts, agriculture still has and will have a major role in income production and the ease of social tensions in rural areas in the future as well. Hungary’s accession to the European Union provides new chances and new prospects for Hungarian agriculture and rural areas. Hungarian agriculture became a part of the internal market which includes about 450 million people. The safety of marketing became stronger, the rate of financial support is increasing and the income of growers will increase in the future. This process implies more obligations and the keeping of strict regulations. Competition inside the internal market is intensifying, competitiveness will be more important while the chances of development and investment of the growers and the feasibility of more effective land use are increasing. After the accession, integration into the directives formulated in the CAP and the packages of measures accepted in it is framework have growing importance.These directives encourage farm-reallocation, namely the rational estate concentration. In general, it can be stated that rational estate concentration, and more effective land use as a consequence, will increase the efficiency of agricultural production.